An Honest Peace Broker? Malaysia as a Third Country Facilitator of Peace Building Process in the Southern Philippines - Suriya Ahmad Apandi, Laila; Omar, Rusdi; Rahim Anuar, Abdul (International Journal of Engineering and Technology, 2018)
Since its involvement as the third country facilitator of peace building process in Southern Philippines in 2001, Malaysia has often been criticized on the grounds of sympathizing the Moro Islamic Liberation Front, stake of national interest concerning the Sabah issues and inefficient conduct of facilitator. This suggests the controversial role of Malaysia as a third country facilitator of peace building process in the form of biased peace facilitator. The paper, therefore, aims to examine whether Malaysia is an honest peace broker when facilitating the peace process building in Southern Philippines by examining its exercise of impartiality and equidistance.Â  It further argues that two integral factors of foreign policy contribute to the honest role of Malaysia as a peace broker in Southern Philippines; peaceful co-existence and non-interference. The findings show that Malaysia is an honest broker by exercising impartiality and equidistance when facilitating the peace building process in the Southern Philippines.Â